Late Victorian Orientalism : representations of the East in nineteenth-century literature, art and culture from the Pre-Raphaelites to John La Farge - Sasso, Eleonora; Sasso, Eleonora (Anthem nineteenth-century series, 2020)
IntroductionEleonora SassoFitzGerald's timelinesRobert Douglas-FairhurstEmpires and scapegoats: the pre-Raphaelites in the near EastFlorence S. BoosAja'ib, mutalibun and hur al-ayn: Rossetti, Morris, Swinburne and the Arabian nightsEleonora SassoThe use of contradictions in John La Farge's prismatic syncretismAndrea Mariani'Strange webs with Eastern merchants': the Orient of aesthetic poetryElisa BizzottoMiriam SetteBorrowed verses: code and representation within the first travelogue of the city of Hong Kong, 1841-42Christopher CowellNewby and Thesiger: humour and lament in the Hindu KushBen CockingThe exoticism of Téchine's Les Sœurs Brontë: the dream of an impossible elsewhereFabrizio Impellizzeri